Contrasting Effects of Nitrogen Input on Soil Carbon Pools in Arid and Humid Climates - Shibing Jia; Cuihuan Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Guopeng Liang; Han Li; Li Zhang; Lin Xu; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Global Change Biology, 2026)
Nitrogen (N) input affects soil organic carbon (SOC) dynamics and storage by specifically influencing the light (LFOC) and heavy fractions of organic C (HFOC). While the effects of N input on SOC pools are known, its specific influence in arid and humid regions remains unresolved, although it is critically important to predict carbon–climate feedback and SOC accumulation. We conducted a meta‐analysis of 881 paired observations from 60 studies to quantify the climate‐specific responses of SOC, LFOC, and HFOC contents to N input, thereby revealing distinct effects in arid versus humid regions. N input increased the LFOC content by 25% in arid regions, whereas the HFOC and SOC contents remained unchanged. This LFOC accumulation may reflect increased plant C inputs, suppressed microbial decomposition, and strong physical protection compared with soil without N input. Conversely, in humid regions, N input increased the HFOC and SOC contents by 10%. These increases were associated with the following four mechanisms: (1) increases in plant and microbial necromass production after N input, (2) microbially‐mediated formation of the HFOC from the LFOC, (3) accelerated lignin‐derived C accumulation due to suppressed saprotrophic fungal decomposition, and (4) raised physico–chemical stabilization by various biotic and abiotic mechanisms. Specifically, increases in LFOC content in arid regions occurred under medium to high N input rates (≥ 50 kg N ha −1 year −1 ), whereas increases in HFOC and SOC contents in humid regions occurred only under medium N input (50–100 kg N ha‐1 year −1 ). These increases occurred primarily after periods of N input longer than 5 years and mainly in topsoil (

Co-pyrolysis-to-co-gasification continuum of Pennisetum hydridum and waste tires: Temperature/atmosphere/synergy characterization of tar/char/gas products - Sen Lin; Xin Chen; Guopeng Ke; Jingyong Liu; Zhibin Chen; Leyao Tao; Weijie Li; Fatih Evrendilek; Sheng Zhong; Zuoyi Yang; Yao He; Liangzhong Li (Journal of Cleaner Production, 2026)

Vibration Features of the Aft Shafting Subjected to Semi-Submerged Propeller Hydrodynamic Excitation - Xiaoqing Yin; Junhong Zhang; Jiewei Lin; Huwei Dai; Guopeng Wu (Journal of Marine Science and Engineering, 2026)
To reduce the adverse effects of stern-shaft system vibration on ship performance, this work combined hydrodynamic excitations calculated for a semi-submerged propeller and established a multibody dynamics (MBDs) model of the stern shaft system that included a flexible shaft, propeller, and elastically damped support bearings. The MBDs model’s accuracy was verified through comparison between experimentally identified modal parameters and those computed by the model. It was found that the bearing stiffness and the hydrodynamic excitation frequency collectively determine the vibration amplitude and modal shape of the shaft system, based on an analysis of varied bearing stiffness and damping. Bearing displacement had a significant impact on shafting vibration. And the tie rod with a stiffness of 2.5 × 107 N/m provided a noticeable vibration damping effect. The findings offered theoretical support for mitigating stern-shaft vibration in high-speed vessels subjected to hydrodynamic excitation from semi-submerged propellers.

Digital simulation of condensation and water loss in ventilated lychee packaging - Jicheng Lin; Xiaodan Zhang; Yihong Jiang; Dongfeng Liu; Wei Cai; Guopeng Lin; Zhiwu Ding; Enli Lü; Jiaming Guo (Biosystems Engineering, 2025)

Interactive effects of warming and drought on soil organic carbon sequestration and methane uptake in straw and biochar amended soils: Mechanisms and global implications - Jitong Lin; Guopeng Liang; Marcela Hernández; Zhiyu Xu; Yinghao Xue; Renhua Sun; Yuanfeng Sun; Lulu Dai; Yanhong Lou; Haojie Feng; Hui Wang; Quangang Yang; et al. (Chemical Engineering Journal, 2025)

Nuclear-localized metabolic enzymes: emerging key players in tumor epigenetic regulation - Limei Chen; Zhihui Wu; Weixi Yuan; Nan Chen; Peina Lin; Senyi Liao; Guopeng Xie (Molecular and Cellular Biochemistry, 2025)

The increase of microbial diversity enhances the compensatory thermal adaptation of soil microbial respiration - Zhengyi Huang; Yangui Su; Sinuo Lin; Guopeng Wu; Hao Cheng; Jingyi Yan; Gang Huang (Applied Soil Ecology, 2025)

Synergistic atmospheric influence on the co-pyrolysis of antibiotic sludge and waste bicycle tires: Optimal drivers, products, and pathways - Dajie Jia; Tao Chen; Liangzhon Li; Jingyong Liu; Zhibin Chen; Sen Lin; Guopeng Ke; Fatih Evrendilek; Wuming Xie; Wenxiao Huang; Chenyu Yang (Journal of Hazardous Materials, 2025)

Dietary nucleotides drive changes in infant fecal microbiota in vitro and gut microbiota-gut-brain development in neonatal rats: A potential “nitrogen source” for early microbiota growth - Zhihao Qu; Bo Zhang; Guopeng Lin; Min Guo; Peijun Tian; Linlin Wang; Wei Chen; Heng Zhang; Gang Wang (Food Chemistry, 2025)

Imbalances in the gut microbiota and metabolome are associated with functional constipation in pregnancy - Ruili Pan; Ying Chen; Guopeng Lin; Haojue Wang; Xiaopeng Xu; Linlin Wang; Peijun Tian; Jianxin Zhao; Wei Chen; Gang Wang (Food Bioscience, 2024)

Changes in soil organic carbon stocks and its physical fractions along an elevation in a subtropical mountain forest - Guopeng Wu; Gang Huang; Sinuo Lin; Zhengyi Huang; Hao cheng; Yangui Su (Journal of Environmental Management, 2024)

Elevational patterns of microbial carbon use efficiency in a subtropical mountain forest - Guopeng Wu; Yangui Su; Jingjing Wang; Sinuo Lin; Zhengyi Huang; Gang Huang (Biology and Fertility of Soils, 2024)

The scaling of leaf nitrogen and phosphorus along a phosphorus availability gradient in a subtropical forest - Jiahao Wen; Janice Brahney; Yaoben Lin; Zhiliang Ma; Ningxiao Sun; Ji Zheng; Huawei Ji; Hongzhang Kang; Baoming Du; Guopeng Liang; Muhammad Umair; Chunjiang Liu (Plant Ecology, 2022)